Effects of attribution retraining on the perceived career barriers of undergraduate nursing students - Mei-chun Wu; Yan-ping Wu; Yan-ping Wan; Ying Zeng; Xi-rong Tang; Lu-rong Wang (Elsevier, 2015)
Background/purpose: To evaluate the effects of attribution retraining on the perceived career barriers of undergraduate nursing students and to foster positive attributional styles. Methods: Ninety-four undergraduate nursing students were recruited and randomly divided into two groups: the attribution retraining group and the control group. All students were assessed by the perceived career barriers inventory before and after the eight-week study. Results: Attribution retraining significantly influenced the students' perceived career barriers. The mean scores of vocational knowledge, professional knowledge, and social ability of the experimental group were significantly reduced compared to the control group (p < 0.05). Conclusion: Attribution retraining provides opportunities for improving the undergraduate nursing students' vocational knowledge, professional knowledge, and social ability. Attribution retraining should be encouraged in undergraduate nursing programs in order to reduce the nursing shortage in mainland China.